Descrição cariotípica de possíveis novas espécies do complexo Hypostomus ancistroides e outros Hypostominae - Endo, Kátia Sayuri; Martinez, Emanuel Ricardo Monteiro [UNESP]; Zawadzki, Claudio Henrique; de Souza Paiva, Luiz Ricardo [UNESP]; Júnior Júlio, Horácio Ferreira (Universidade Estadual de Maringa, 2012)
Cytogenetic analyses were performed in four species of the Hypostominae subfamily, three from Hypostomus (Hypostomini) genus and Rhinelepis aspera (Rhinelepini). Three populations of Hypostomus ancistroides were analyzed, which had 2n=68 chromosomes, but presented different karyotype formulas. Hypostomus regani and H. strigaticeps, both from Ivaí river, showed 2n=72 chromosomes with two distinct cytotypes. In turn, R. aspera of the upper Paraná river basin presented 2n=54 chromosome. Multiple Nucleolar Organizer Regions (NORs) have been evidenced by silver nitrate staining in species of Hypostomus and single NOR in R. aspera. The observed variation in the chromosome number and the marked variability in karyotype formulas and NORs reveal a certain amount of karyotype variation in the genus Hypostomus suggesting the probable existence of cryptic species with independent chromosome traits. Therefore, our data can be of great value in discriminating species and understanding their chromosomal evolution.
Karyotype description of possible new species of the Hypostomus ancistroides complex (Teleostei: Loricariidae) and other Hypostominae
Keywords: Chromosomal evolution; Cryptic species; Neotropical fishes; NOR; silver nitrate; chromosome analysis; chromosome NOR; chromosome number; chromosome variant; cytogenetics; female; genetic trait; Hypostomus; Hypostomus ancistroides; karyotype; male; new species; nonhuman; population genetics; population research; Rhinelepis aspera; river basin; teleost; Hypostomus regani; Loricariidae; Pisces; Teleostei